2022
DOI: 10.1111/dth.15535
|View full text |Cite
|
Sign up to set email alerts
|

Brightening effect of Ziziphus jujuba (jujube) fruit extract on facial skin: A randomized, double‐blind, clinical study

Abstract: Ziziphus jujuba Mill. (jujube) is an invaluable medicinal plant in traditional and modern medicine. Jujube syrup is a complex of herbal extracts including Z. jujuba, Berberis vulgaris, Rhus coriaria, Prunus domestica, and Rosa damascene. The purpose of the present study was to formulate and investigate the efficacy and safety of jujube syrup on brightening of facial skin. In this randomized, double‐blind, controlled clinical study, 46 participants consumed jujube syrup or placebo (23 in each group) twice a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…No estudo clínico realizado por Aafi et al (2022), foi investigado a eficácia do xarope de Ziziphus jujuba (jujuba) no tratamento da hiperpigmentação facial. Este estudo foi conduzido com rigor, seguindo um desenho randomizado, duplo-cego e controlado.…”
Section: Resultsunclassified
“…No estudo clínico realizado por Aafi et al (2022), foi investigado a eficácia do xarope de Ziziphus jujuba (jujuba) no tratamento da hiperpigmentação facial. Este estudo foi conduzido com rigor, seguindo um desenho randomizado, duplo-cego e controlado.…”
Section: Resultsunclassified
“…No estudo clínico realizado por Aafi et al (2022), foi investigado a eficácia do xarope de Ziziphus jujuba (jujuba) no tratamento da hiperpigmentação facial. Este estudo foi conduzido com rigor, seguindo um desenho randomizado, duplo-cego e controlado.…”
Section: Resultsunclassified
“…Several studies have demonstrated that jujube has a wide range of pharmacological activities in the cardiovascular and nervous systems as well as antioxidant, anti-inflammatory and anticancer properties (Alsayari and Wahab 2021;Chen and Tsim 2020;Lu et al 2021). In addition, clinical studies have reported that jujube is effective and safe for treating human skin hyperpigmentation (Aafi et al 2022). Moreover, cinnamon (Lauraceae) has been traditionally used as a food flavoring and remedy for various ailments (Hamidpour et al 2015), and its extracts have antioxidant, anti-inflammatory, astringent, digestive, antiseptic, thermostimulant, carminative, blood purifying, antifungal, antiviral, antibacterial, and immunomodulatory properties (Hamidpour et al 2015;Shang et al 2021).…”
Section: Discussionmentioning
confidence: 99%